Humoral response to BNT162b2 and coronaVac in patients undergoing maintenance hemodialysis: A multicenter prospective cohort study - TUĞCU, MURAT; TUĞLULAR, ZÜBEYDE SERHAN (My University, 2023)
Introduction: Data regarding inactivated vaccines for SARS-CoV-2 in patients undergoing maintenance hemodialysis (MHD) are limited. We aimed to investigate humoral responses induced by CoronaVac compared to BNT162b2 in this population. Methods: In this multicenter prospective cohort study, adult patients undergoing MHD who lacked a history of COVID-19 and decided to get vaccinated with BNT162b2 or CoronaVac were enrolled. Participants provided serum samples before, 1 and 3 months after 2 doses. Anti-SARS-CoV-2 IgG antibodies against receptor-binding domain of the virus were measured, and levels >= 50 AU/mL were considered as positive. Breakthrough infections and adverse events were recorded. Results: Ninety-two patients were included, 68 (73.9%) of whom were seronegative at baseline. BNT162b2 and CoronaVac were administered in 38 (55.9%) and 30 (44.1%) patients. At 1 month, seropositivity was 93.1% in BNT162b2 and 88% in CoronaVac groups (p = 0.519). Quantitative antibody levels were significantly higher in BNT162b2 (p < 0.001). At 3 months, both seropositivity (96.4% and 78.3%, p = 0.045) and antibody levels (p = 0.001) remained higher in BNT162b2 compared to CoronaVac. Five patients (7.4%) experienced breakthrough COVID-19. Adverse events were more frequent with BNT162b2, although all of them were mild. Multiple linear regression model showed that only vaccine choice (BNT162b2) was related to the humoral response (beta = 0.272, p = 0.038). Seropositive patients at baseline (n = 24) had higher antibody levels at any time point. Conclusions: BNT162b2 and CoronaVac induced humoral responses in naive patients undergoing MHD, which were more robust and durable for 3 months after BNT162b2. Both vaccines created high antibody levels in patients who were seropositive at baseline.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; COVID-19; Dialysis; Hemodialysis; SARS-CoV-2; Vaccine; DIALYSIS PATIENTS; MESSENGER-RNA; KIDNEY-TRANSPLANT; IMMUNOGENICITY; MORTALITY; VACCINES